Optimalisasi Manajemen Sumber Daya Manusia di Madrasah Pendidikan Agama Islam Medan - Syukri, Makmur; Pohan, Hadi Lapian (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
This research examines the implementation of Human Resources Management (HRDM) in Islamic Religious Education Madrasahs in Medan, North Sumatra. The aim is to analyze HRM practices, identify challenges, and formulate optimization strategies in the context of Islamic education. Using a qualitative approach with a case study method, data was collected through in-depth interviews, direct observation and document analysis. This research reveals that madrasas have implemented several good HRM practices, such as HR planning based on needs analysis and professional development programs. However, significant challenges were found such as budget limitations, lack of HR experts, and resistance to change. Based on these findings, the research proposes optimization strategies, including increasing budget allocation for human resource development, collaboration with universities, and implementing a more comprehensive performance management system. Research concludes that HRM has a vital role in improving the quality of education in madrasas. Even though there are challenges, with the right strategy, HRM can be optimized to support the achievement of Islamic education goals. The contribution of this research is significant to the Islamic education management literature, especially HRM in madrasas. Further research is needed to examine the effectiveness of HRM strategies in a broader context and their impact on student achievement and the overall quality of education.